Molecular characterization of dengue virus serotype 1 infections in French travelers from Africa between 2013 and 2019 - Fourié, Toscane; Durand, Guillaume André; Touret, Franck; Piorkowski, Géraldine; Dubot-Pérès, Audrey; de Lamballerie, Xavier; Leparc-Goffart, Isabelle; Grard, Gilda (Frontiers in Virology, 2023)
Laboratory-confirmed dengue virus (DENV) infections in Africa are rarely reported. In this study, we report 18 DENV serotype 1 (DENV-1) infections, diagnosed by the French National Reference Center for Arboviruses, in patients who had histories of recent travel in Africa. Our analyses revealed two cases, one from Niger in 2018 and one from the Republic of the Congo in 2016, where dengue fever had not been previously reported, and one case from Mauritania in 2015, where DENV-1 had not been previously reported. These cases support the reported spread of DENV outside its well-established tropical and subtropical environment toward the arid deserts of the Sahel. Phylogenetic analyses suggest that a single monophyletic DENV-1 lineage is currently in circulation in West Africa, having spread from East Africa after its original importation from Asia. Our study provides an improved understanding of DENV dynamics in Africa and underlines the importance of surveillance of travel-acquired infections.